A definition of bioinks and their distinction from biomaterial inks. (23rd November 2018) - Groll, J; Burdick, J A; Cho, D-W; Derby, B; Gelinsky, M; Heilshorn, S C; Jüngst, T; Malda, J; Mironov, V A; Nakayama, K; Ovsianikov, A; Sun, W; et al.
Abstract: Biofabrication aims to fabricate biologically functional products through bioprinting or bioassembly (Groll et al 2016 Biofabrication 8 013001). In biofabrication processes, cells are positioned at defined coordinates in three-dimensional space using automated and computer controlled techniques (Moroni et al 2018 Trends Biotechnol. 36 384–402), usually with the aid of biomaterials that are either (i) directly processed with the cells as suspensions/dispersions, (ii) deposited simultaneously in a separate printing process, or (iii) used as a transient support material. Materials that are suited for biofabrication are often referred to as bioinks and have become an important area of research within the field. In view of this special issue on bioinks, we aim herein to briefly summarize the historic evolution of this term within the field of biofabrication. Furthermore, we propose a simple but general definition of bioinks, and clarify its distinction from biomaterial inks.